Bio-butanol as a new generation of clean alternative fuel for SI (spark ignition) and CI (compression ignition) engines. (March 2020) - Zhen, Xudong; Wang, Yang; Liu, Daming
Abstract: Bio-butanol (N-butanol) is a renewable, environmentally friendly, and economical alternative fuel that, like many other alternative fuels such as methanol, ethanol, and natural gas, is also considered to be one of the most advantageous fuels to replacement for conventional petroleum fuels (such as gasoline or diesel fuel). Bio-butanol fuel has recently been used as an alternative fuel to conventional fuels for IC engines (gasoline or diesel engines) to meet some environmental and economic considerations. Compared with conventional fuels (gasoline and diesel fuels), bio-butanol has many advantages, so it has the potential to reduce vehicle emissions, thereby improving the atmospheric environment, reducing energy demand pressure, and significantly decreasing the car's dependence on non-renewable resource. The research and application of bio-butanol have made great progress in the past few years, so it is worth to summarize and analyze the application of bio-butanol in IC engines. This paper systematically introduces the application of bio-butanol fuel in SI and CI engines, and summarizes the application methods of bio-butanol/gasoline, bio-butanol/diesel and other mixed fuels on SI and CI engines. Finally, some suggestions for the future research and development direction of bio-butanol engines are put forward in study. Highlights: The production methods, marketing and the properties of bio-butanol were summarized. In SI and CI engines, bio-butanol has a position effect on fuel consumption and emissions. At present, the bio-butanol mixed combustion method is widely used in SI and CI engines. This paper put forward some new suggestions in the researches of bio-butanol engine in the future. To meet environmental and energy balance considerations, bio-butanol has a bright future in SI and CI engines.